Prototipe Promosi Jabatan Karyawan Berdasarkan Hasil Optimalisasi Komparasi Algoritma Data Mining (C4.5 Dan Neural Network) Berbasis Particle Swarm Optimization : Studi Kasus PT. Karya Tangkas Mandiri - Nurcahya, Saputra Dwi (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2024)
Abstract - Optimizing the quality of human resources for the company is required to reach the vision and mission of the company. Therefore, improvement of services can begin with making the right decisions quickly and objectively, so that the outcome will be a good contribution also for companies. Development of Information Technology Systems today are very helpful in the development of an accurate decision-making systems. PT Karya Tangkas Mandiri is a national private company engaged in the provision of security services, consulting and expeditions ,that  very closely with Human Resources issues follow the needs of service users, resulting in frequent change of position. It would require an objective decision-making model in the promotion of employees on company, to help the managerial decisions quickly and accurately. This research using the method Comparative assesment of algorithms C4.5, bayessian classifier and Neural Network based on Particle Swarm Optimization using Rapid Miner software by comparing several classifications. Results of this research was to produce a model or protoype that can support the decision making in regards to determining promotion department employees objectively and to meet the challenges of the world today's business.Keywords: C4.5, neural network, Particle Swarm Optimization, Rapidminer, Prototype, Data Mining, Promotional Title